2002
DOI: 10.1186/gb-2002-3-3-reviews1006
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: When pre-mRNAs are spliced, a multi-component complex is deposited onto them, close to the sites of intron removal. New findings suggest that these exon-exon junction complexes and the complexes that bind mRNA caps are key effectors of the fate of spliced mRNAs and may regulate whether mRNAs containing premature stop codons are degraded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 36 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Western blot analysis on the protein extracts obtained from AML blasts of two mutants (#2236 and 3102) failed to show the expression of truncated ETV6 proteins. Generally, the absence of abnormal protein is justified by the possible degradation of mutant transcripts through a nonsense-mediated mRNA decay pathway (Losson and Lacroute, 1979;Frischmeyer and Dietz, 1999;Schell et al, 2002). Nucleotide sequence analysis on patient #2236 demonstrated that the mutant transcript level was decreased to only one-third of the wt level (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Western blot analysis on the protein extracts obtained from AML blasts of two mutants (#2236 and 3102) failed to show the expression of truncated ETV6 proteins. Generally, the absence of abnormal protein is justified by the possible degradation of mutant transcripts through a nonsense-mediated mRNA decay pathway (Losson and Lacroute, 1979;Frischmeyer and Dietz, 1999;Schell et al, 2002). Nucleotide sequence analysis on patient #2236 demonstrated that the mutant transcript level was decreased to only one-third of the wt level (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Our experimental data further indicate that human U2AF 35 c mRNAs are targeted to NMD, a mechanism by which cells selectively recognize and degrade mRNAs that contain premature termination codons (for recent reviews see Refs. [52][53][54] surveillance mechanism that destroys aberrant mRNAs generated as a result of biosynthetic errors or gene mutations, it was recently proposed that NMD additionally participates in a pathway that controls expression of a large number of genes (5). Based on a bioinformatic approach, Lewis et al (5) predicted that 35% of human EST-suggested alternative isoforms contain premature termination codons and are potential targets for NMD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the EJC contains several proteins involved in NMD, including the well-characterized NMD proteins UPF2 and UPF3b (80). Together with several other lines of evidence (7,(81)(82)(83), a strong case can be made for the idea that the EJC relays the previous location of introns relative to the stop codon to ultimately dictate whether or not rapid mRNA decay will be elicited.…”
Section: Nmd and The Exon-junction Complexmentioning
confidence: 99%